Advances in autophagy as a target in the treatment of tumours. (7th February 2022) - Li, Yingying; Gao, Shan; Du, Xiyou; Ji, Jianbo; Xi, Yanwei; Zhai, Guangxi
Abstract: Autophagy is a multi-step lysosomal degradation process, which regulates energy and material metabolism and has been used to maintain homeostasis. Autophagy has been shown to be involved in the regulation of health and disease. But at present, there is no consensus on the relationship between autophagy and tumour, and we consider that it plays a dual role in the occurrence and development of tumour. That is to say, under certain conditions, it can inhibit the occurrence of tumour, but it can also promote the process of tumour. Therefore, autophagy could be used as a target for tumour treatment. The regulation of autophagy plays a synergistic role in the radiotherapy, chemotherapy, phototherapy and immunotherapy of tumour, and nano drug delivery system provides a promising strategy for improving the efficacy of autophagy regulation. This review summarised the progress in the regulatory pathways and factors of autophagy as well as nanoformulations as carriers for the delivery of autophagy modulators.